(untitled) (Journal of Dhaka Medical College, 2015)
Isolated infundibular pulmonary stenosis (IIPS) in adult is an uncommon cardiac abnormality. Infundibular pulmonary stenosis leading to right ventricular hypertrophy is a big problem. Early excision of hypertrophied muscular band can overcome this problem. In our case report we have done excision of pulmonary infundibular muscle band of a late case of isolated pulmonary infundibular stenosis. And our patient showed a good response after excision of infundibular muscle band. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22711 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 140-142